RANCANG BANGUN SISTEM PEMESANAN WEDDING ORGANIZER MENGGUNAKAN METODE RAD DI SHOFIA AHMAD WEDDING - Tri Wulandari; Siti Nurmiati (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2022)
The development of information technology today is experiencing very rapid progress. This technological development is marked by processing in the field of work that was originally done offline, but has now been managed using modern methods. Wedding Organizer is a service that is used to help brides and grooms prepare for a wedding at Shofia Ahmad Wedding still does it manually the bride and groom must come directly to the WO location to ask about prices, and are still recording transactions that are done manually using paper so that less effective. This study uses the Rapid Application Development (RAD) method using PHP as the programming language and UML as the design process. This research results in a system that can order wedding packages through the website and can see the products/wedding packages provided and the prices of each wedding package available at Shofia Ahmad Wedding. Keywords: Wedding Organizer, RAD, PHP.